Scorpion toxin BmK I directly activates Nav1.8 in primary sensory neurons to induce neuronal hyperexcitability in rats. Issue 6 (24th April 2015) - Ye, Pin; Jiao, Yunlu; Li, Zhenwei; Hua, Liming; Fu, Jin; Jiang, Feng; Liu, Tong; Ji, Yonghua
Abstract: Voltage-gated sodium channels (VGSCs) in primary sensory neurons play a key role in transmitting pain signals to the central nervous system. BmK I, a site-3 sodium channel-specific toxin from scorpion Buthus martensi Karsch, induces pain behaviors in rats. However, the subtypes of VGSCs targeted by BmK I were not entirely clear. We therefore investigated the effects of BmK I on the current amplitude, gating and kinetic properties of Nav 1.8, which is associated with neuronal hyperexcitability in DRG neurons. It was found that BmK I dose-dependently increased Nav 1.8 current in small-sized (<25 μm) acutely dissociated DRG neurons, which correlated with its inhibition on both fast and slow inactivation. Moreover, voltage-dependent activation and steady-state inactivation curves of Nav 1.8 were shifted in a hyperpolarized direction. Thus, BmK I reduced the threshold of neuronal excitability and increased action potential firing in DRG neurons. In conclusion, our data clearly demonstrated that BmK I modulated Nav 1.8 remarkably, suggesting BmK I as a valuable probe for studying Nav 1.8. And Nav1.8 is an important target related to BmK I-evoked pain.